Mapping the links between climate change and human health in urban areas: how is research conducted? A Scoping review protocol - Hiago Pereira Barbosa; Anne Roué-Le Gall; Clément Deloly; Jean-Philippe Regnaux; Marie-Florence Thomas (BMJ Open)
Introduction Scientists from a wide variety of fields of knowledge are increasingly interested in climate change issues. The importance given to the phenomenon is explained by the uncertainties surrounding it and its consequences not yet fully known. However, there is wide agreement that human activities are modifying the Earth’s climate beyond the natural cyclical changes and that these changes impact human health. This scoping review aimed to understand how research on the links between climate change and human health in urban areas is conducted and how this research is approached holistically or not.Methods and analysis This scoping review is mainly guided by the Arskey and O’Malley scoping review framework. A broad range of databases will be used, including PubMed, ScienceDirect, Web of Science Core Collection, GreenFILE and Information Science & Technology Abstracts. Predefined inclusion and exclusion criteria will be used, with a focus on climate change and human health outcome studies published between January 1990 and July 2019. An interdisciplinary team has formulated search strategies and the reviewers will independently screen eligible studies for final study selection. We will apply a thematic analysis to evaluate and categorise the study findings. We expect to map the research according to the scientific research methods, the scientific fields and the determinants of health studied. Along these lines, we will be able to understand how holistic the research is.Ethics and dissemination No primary data will be collected since all data presented in this review are based on published articles and publicly available documents. Therefore, ethics committee approval is not a requirement. The findings will be disseminated through publication in a peer-reviewed journal, presentations at conferences relevant to the field of this research, as well as presentations to relevant stakeholders.